ANALISA POLA PEMBELIAN KONSUMEN MENGGUNAKAN ALGORITMA APRIORI DI JOIN MART - Sinaga, Dewi Febryanti Sesilia; Elisa, Erlin (LPPM Universitas Putera Batam, 2021)
Data mining is a science whose job is to find, explore, or mining knowledge from the data or information we have. With the information, it can be used to make a decision because information is very important for everyone, including for minimarket businesses such as Join Mart. This Join Mart is very close to the shopping center in Batam City, then it can affect the increase in sales every day and make the pile of data in database more and more. Basically, pile of data is better processed so that it becomes one of the useful business defense strategies for Join Mart. Analyzing purchasing patterns using apriori algorithm can find the relationship of each item and find out each item that appears simultaneously. In this study, the highest item results were found in Oil, Salt, and Flavors with a supporting value of 20.00% each while Confidence was 100.00%.